Welding of Dissimilar Steels via Thixowelding Processes - Mohammed, M. N.; Omar, M. Z.; Alhawari, K. S.; Abdelgnei, M. A.; Al-Zubaidi, Salah (International Journal of Engineering and Technology, 2018)
In several circumstances, traditional welding processes cannot produce sound weldments especially for high grade materials. In this research, a dissimilar joint of AISI D2-AISI 304 steels was produced by using new semi-solid joining process. The achieved findings revealed the quality of dissimilar joints compared with other welding processes. During Metallographic investigation, neither oxides nor micro-cracks were observed along the interface of semi-solid joint. This study confirmed that the development of dendritic structure was avoided and high quality joint can be obtained.